Electrospinning of polycaprolactone nanofibers using H2O as benign additive in polycaprolactone/glacial acetic acid solution. Issue 3 (20th September 2017) - Li, Wenchao; Shi, Lei; Zhang, Xianglin; Liu, Kang; Ullah, Ismat; Cheng, Penghua
ABSTRACT: Considerable efforts have been devoted to the production of polycaprolactone (PCL) nanofibrous structures by electrospinning. However, some toxic solvents have often been used to achieve bead‐free nanofibers. At present, a benign solvent such as glacial acetic acid (GAC) only leads to beaded or microscale fibers. Therefore a study is done to extend the electrospinnability of the PCL/GAC system by the addition of H2 O. The solution properties of conductivity, viscosity, and surface tension were altered by the addition of H2 O, especially increasing the conductivity and viscosity. These properties essential to electrospinning could remain stable for 6 h when the H2 O content was less than or equal to 9 vol %. Then ultrafine PCL fibers with diameters from 188 to 200 nm, 10 times smaller than when dissolved in pure GAC, were electrospun from solutions of PCL with concentrations in the range of 17 to 20 wt % with H2 O content at 9 vol %. Finally, the crystallinity and crystallite size of the resulting fibers were smaller than that of raw PCL pellets. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45578. Abstract :